2022
DOI: 10.21037/jtd-22-193
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of left ventricular hypertrophy in postoperative outcomes in type A acute aortic dissection

Abstract: Background: Left ventricular hypertrophy (LVH) is common in hypertension patients. Hypertension is a recognized risk factor of acute aortic dissection. This study aimed to explore the prognostic value of LVH in predicting postoperative outcomes in type A acute aortic dissection (ATAAD) patients.Methods: This was a single-central retrospectively designed study. One hundred and ninety-three ATAAD patients who underwent surgical repair at Renmin Hospital of Wuhan University from January 2018 to November 2021 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Additionally, left ventricular hypertrophy was identified as an important risk factor for postoperative complications and mortality. Zuo et al suggested that left ventricular hypertrophy is a risk factor for aortic enlargement and subsequent dissection [17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, left ventricular hypertrophy was identified as an important risk factor for postoperative complications and mortality. Zuo et al suggested that left ventricular hypertrophy is a risk factor for aortic enlargement and subsequent dissection [17].…”
Section: Discussionmentioning
confidence: 99%
“…The association between LVH and AD is surely an important issue to understand the physiology of AD. Given limitation from the retrospective observational study, however, inconvenience in the evaluation of the present study exists ( 9 ). First, too many factors were included in the multivariable risk analyses for only 38 of primary outcomes.…”
mentioning
confidence: 98%
“…In the journal, Zuo and his colleagues reviewed 193 patients who underwent AD repair from 2018 to 2021 in their institute ( 9 ). Scope of the study was to evaluate impacts of left ventricular hypertrophy (LVH) on clinical outcomes (55 versus 138 patients with/without LVH).…”
mentioning
confidence: 99%
“…In their study titled “Prognostic value of left ventricular hypertrophy in postoperative outcomes in Type A acute aortic dissection”, Zuo and colleagues ( 5 ) from Wuhan, China analyzed the utility of LVH in predicting postoperative outcomes in patients with acute aortic Type A dissection (ATAAD). This was a retrospective, single-center analysis of 193 patients who underwent ATAAD surgical repair over a nearly four-year period.…”
mentioning
confidence: 99%
“…The incidence of composite major outcomes (CMO), which included operative mortality, stroke, paraplegia, dialysis, and adverse cardiac events, was 30.9% in patients with LVH vs. 15.2% in patients without LVH. The LVH group had higher operative mortality (18.2% vs. 7.2%) and higher incidences of postoperative stroke, low cardiac output syndrome, and ventricular arrhythmias ( 5 ).…”
mentioning
confidence: 99%